Process for the preparation of morphologically stable s-shaped intervention micro-wires
Patent Information
- Application Number
- CN202611376214.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-07
- Publication Date
- 2026-10-09
AI Technical Summary
但是聚四氟乙烯涂层的耐磨性较差,在使用过程中因结构损坏会出现疏水性能下降等问题,且由于此类低黏附特性涂层自身与微导丝的结合强度不高,在临床使用过程中容易发生因涂层脱落导致的严重事故,给患者造成致命性的影响,由此可见,必须采取更加全面、合理的表面改性手段,使得微导丝表面涂层在具有良好疏水性的前提下,不但具有良好的附着力和牢固度,而且具有良好的生物相容性和抗菌抑菌性
本发明利用腰果酚缩水甘油醚与丙烯酸发生开环反应制备腰果酚基丙烯酸酯,然后利用腰果酚基丙烯酸酯、双键基多巴胺和双键基松香酸进行聚合反应制备得到功能化聚合物,其中双键基多巴胺作为粘合剂,利用其贻贝仿生特性可强化涂层与基底材料的结合力,双键基松香酸作为疏水单元,其含有疏水的氢化菲环结构展现出良好的疏水性能,腰果酚基丙烯酸酯作为生物基光固化活性单体,其侧链分子上的不饱和双键参与UV固化交联,与巯基有机硅树脂发生巯基-烯点击反应,构建聚合物主网络,且其分子结构中独特的刚性苯环与柔性长链相结合赋予固化涂层良好的力学强度与柔韧性平衡,该功能化聚合物通过腰果酚基丙烯酸酯、双键基多巴胺和双键基松香酸的共聚反应,展现出良好的粘附性能,能够牢固附着于基底材料表面,从而确保涂层紧密覆盖基底材料,其中巯基有机硅树脂利用甲基三甲氧基硅烷、二甲基二甲氧基硅烷和3-巯丙基三甲氧基硅烷通过水解缩聚合成,其以Si-O-Si为骨架,具备耐候性和低摩擦性,链段柔韧并且由于表面能较低还具有一定的疏水特性。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of interventional medical device technology, specifically relating to the fabrication process of a morphologically stable interventional microguidewire with an S-bend. Background Technology
[0002] Interventional therapy is a minimally invasive treatment using modern high-tech methods. Guided by medical imaging equipment, it involves introducing specialized catheters, guidewires, and other precision instruments into the body for diagnosis and local treatment of lesions. Most interventional procedures are performed within blood vessels, offering advantages such as no incision, minimal trauma, rapid recovery, and low complication rates. Depending on the needs, materials may be stainless steel wire, nickel-titanium shape memory alloy wire, or a combination of both. In clinical procedures, the role of interventional microguidewires is primarily to guide catheters through the epidermis into blood vessels, assist catheters in selectively entering small vascular branches or other disease cavities, or serve as an important tool for catheter replacement. In practical use, the lubricity of the guidewire surface is crucial. Surface lubricating coatings are widely used on the surfaces of interventional devices such as intravascular catheters, guidewires, and delivery systems. Applying lubricating coatings to the surface of vascular interventional devices effectively improves the biocompatibility of the device surface, reduces friction between the device and the blood vessel, minimizes damage to the vessel wall, and allows interventional devices to pass more easily through tortuous blood vessels, thereby reducing the difficulty of the procedure.
[0003] The superior tactile and responsive properties of hydrophobic coated microwires compared to hydrophilic lubricating coatings have led to their wider clinical applications. Hydrophobic coatings often utilize fluoropolymers with low adhesion properties, such as polytetrafluoroethylene (PTFE). However, PTFE coatings have poor abrasion resistance, and structural damage during use can lead to a decrease in hydrophobic properties. Furthermore, due to the weak bonding strength between these low-adhesion coatings and the microwires, serious accidents caused by coating detachment during clinical use can occur, potentially leading to fatal consequences for patients. Therefore, more comprehensive and rational surface modification methods are necessary to ensure that the microwire surface coating, while possessing good hydrophobicity, not only exhibits excellent adhesion and strength but also good biocompatibility and antibacterial / bacteriostatic properties. Summary of the Invention
[0004] To address the shortcomings mentioned in the background technology, the present invention aims to provide a stable process for preparing an interventional microwire with an S-bend. Based on the excellent properties of polytetrafluoroethylene (PTFE), a mixture of hydrophobic-doped co-modified hydroxyapatite, functionalized polymers, mercaptosilicone resin, and waterborne epoxy resin is used. This mixture is then firmly bonded to the surface of the interventional microwire through ultraviolet irradiation and thermosetting. This process exhibits excellent adhesion and antibacterial properties, while also possessing excellent superhydrophobic properties. Furthermore, it maintains excellent performance even after mechanical wear, enhancing the long-term durability of the material and effectively solving the problems of weak adhesion and easy detachment of the coating to the substrate.
[0005] The objective of this invention can be achieved through the following technical solutions: The fabrication process of a morphologically stable interventional microwire with an S-bend includes the following steps: S1. Take 50-75 parts by weight of polytetrafluoroethylene and 15-30 parts by weight of hydrophobic-doped co-modified hydroxyapatite and disperse them in 25-40 parts by weight of anhydrous ethanol to form a uniform suspension. S2. Take 70-90 parts by weight of waterborne epoxy resin, 22-30 parts by weight of curing agent, 20-40 parts by weight of functionalized polymer, 10-25 parts by weight of mercapto silicone resin and 2-2.5 parts by weight of photoinitiator and add them to the suspension. Stir evenly to obtain a superhydrophobic modified coating. S3. The interventional microwire with S-bend is immersed in the superhydrophobic modified coating by dip-coating and pulling method, then transferred to a UV curing machine for photocuring, and then placed in an oven for thermal curing to prepare a morphologically stable interventional microwire with S-bend. The hydrophobic-doped co-modified hydroxyapatite was prepared by synthesizing titanium-doped hydroxyapatite using the sol-gel method, followed by surface modification of the titanium-doped hydroxyapatite using tridecafluorooctyltriethoxysilane; the functionalized polymer was prepared by preparing cashew phenol glycidyl acrylate by ring-opening reaction of cashew phenol glycidyl ether and acrylic acid, followed by polymerization reaction of cashew phenol glycidyl acrylate, dopamine with double bond and rosin acid with double bond; the mercaptosilicone resin was prepared by hydrolytic condensation polymerization of methyltrimethoxysilane, dimethyldimethoxysilane and 3-mercaptopropyltrimethoxysilane.
[0006] Preferably, the interventional microwire is made of stainless steel or nickel-titanium alloy.
[0007] Preferably, the distal end of the interventional microguidewire has a progressive S-bend of 30-45°, and the interventional microguidewire undergoes segmented temperature-controlled heat setting treatment. The segmented temperature-controlled heat setting process is as follows: first, the proximal end is heated at 350-400°C and held for 20-25 minutes, then the distal end is heated at 400-500°C and held for 30 minutes. After forming, a low-temperature aging treatment at 100-150°C for 24 hours is performed to eliminate internal stress.
[0008] Preferably, the curing agent is an amine curing agent; the photoinitiator is 2-hydroxy-2-methyl-1-phenyl-1-propanone.
[0009] Preferably, the method for preparing the functionalized polymer includes the following steps: (1) Cashew phenol glycidyl ether was added to the reactor, followed by hydroquinone and triphenylphosphine. The oil bath temperature was maintained at 85°C. Acrylic acid was slowly added dropwise over 4 hours. After the addition was completed, the reaction was stirred for 6 hours. After the reaction was completed, the product was purified by extraction with ethyl acetate and saturated sodium bicarbonate solution. The organic phase was dried with anhydrous magnesium sulfate. The solvent was evaporated under vacuum at 50°C to prepare cashew phenol acrylate. (2) Dissolve tetraborate and sodium bicarbonate in deionized water, add dopamine hydrochloride and stir to mix evenly, then slowly add a mixed solution of methacrylic anhydride and tetrahydrofuran. After the reaction is complete, filter the mixed solution, add ethyl acetate to the filtrate, adjust the pH value to 2 with hydrochloric acid, separate the organic layer, dry with anhydrous magnesium sulfate and then rotary evaporate to obtain a concentrated solution, add n-hexane to the concentrated solution and mix thoroughly to precipitate a solid precipitate, centrifuge to collect the solid precipitate and dissolve it with ethyl acetate, then wash with n-hexane and vacuum dry to prepare double bond dopamine; (3) Dissolve rosin acid in ethyl acetate, then slowly add a mixed solution of oxaloyl chloride and ethyl acetate under ice bath conditions, and then react at 50°C for 5 h to obtain chlorinated rosin acid. Dissolve hydroxyethyl acrylate and triethylamine in ethyl acetate, then add chlorinated rosin acid, and react at 50°C for 3-5 h. After the reaction is completed, filter to remove the precipitate, collect the solvent layer, wash with saturated brine, and remove the solvent by rotary evaporation to prepare double bond rosin acid. (4) Dissolve cashew phenol acrylate, double bond dopamine and double bond rosin acid in a mixed solution of deionized water and tetrahydrofuran, and then add it to a reactor containing 4-cyano-4-(thiobenzoyl)valerate initiator and react for 3-5 h. After the reaction is completed, the mixture is dialyzed for 24 h in a mixed solution of deionized water and anhydrous ethanol through a 3500 Da dialysis bag, and then dried by rotary evaporation to obtain the functionalized polymer.
[0010] Preferably, the molar ratio of cashew phenol acrylate, dopamine, and rosin acid is 1~2:1~2:3~4.
[0011] Preferably, the preparation method of the mercapto-organic silicone resin includes the following steps: Methyltrimethoxysilane, dimethyldimethoxysilane, 3-mercaptopropyltrimethoxysilane and ethyl acetate were added to a reactor, and the temperature was raised to 50°C. Then, hydrochloric acid and deionized water were slowly added dropwise over 1 hour. The mixture was then kept at 60°C for 3 hours. After the reaction was completed, the organic phase was washed with deionized water until neutral. The solvent was evaporated under vacuum at 50°C to prepare a mercapto-based organosilicon resin.
[0012] Preferably, the mass ratio of methyltrimethoxysilane, dimethyldimethoxysilane, 3-mercaptopropyltrimethoxysilane, hydrochloric acid and deionized water is 1:1.9~2:2.3~2.5:0.1~0.12:1.8~2.
[0013] Preferably, the preparation method of the hydrophobic-doped co-modified hydroxyapatite includes the following steps: ① Dissolve tetrabutyl titanate in deionized water and hydrolyze it to obtain a yellow metatitanic acid precipitate. Then add 50% hydrogen peroxide to the metatitanic acid precipitate and sonicate it with an ultrasonic power of 80W for 10 minutes to obtain a light yellow sol. At the same time, add acetylacetone and reflux at 90°C for 20 minutes to prepare titanium dioxide hydrosol. ② Take hydroxyapatite, deionized water and titanium dioxide hydrosol and stir to react for 4 hours. Then filter and dry the product. Add the dried powder to a planetary ball mill for 10 minutes of grinding. After grinding, sieve through 400 mesh. After sieving, put the powder into a muffle furnace and calcine at 600°C for 40 minutes to prepare titanium-doped hydroxyapatite. ③ Titanium-doped hydroxyapatite was ultrasonically dispersed in anhydrous ethanol to obtain a dispersion. A hydrolysate was prepared by taking tridecafluorooctyltriethoxysilane, ethanol and deionized water. The pH of the hydrolysate was adjusted to 4-6 using acetic acid, and then slowly added to the dispersion. The mixture was placed at 110°C for 24 hours. After the reaction was completed, the mixture was centrifuged, washed and dried to obtain hydrophobic-doped co-modified hydroxyapatite.
[0014] Preferably, the addition ratio of hydroxyapatite, deionized water and titanium dioxide hydrosol is 5g: 17.2~22.5mL: 1.2~3.8mL.
[0015] The beneficial effects of this invention are: This invention utilizes the ring-opening reaction of cashew phenol glycidyl ether with acrylic acid to prepare cashew phenol-based acrylate. Then, a functionalized polymer is prepared by polymerization of cashew phenol-based acrylate, dopamine (with double bonds), and rosin acid (with double bonds). Dopamine (with double bonds) acts as a binder, leveraging its mussel-inspired biomimetic properties to enhance the adhesion between the coating and the substrate. Rosin acid (with double bonds) acts as a hydrophobic unit, exhibiting excellent hydrophobic properties due to its hydrophobic hydrogenated phenanthrene ring structure. Cashew phenol-based acrylate, as a bio-based photocurable active monomer, participates in UV curing crosslinking via unsaturated double bonds on its side chains, undergoing a thiol-alkene click reaction with thiol-based silicone resin to construct the polymer backbone. The complex, with its unique combination of rigid benzene rings and flexible long chains in its molecular structure, endows the cured coating with a good balance of mechanical strength and flexibility. This functionalized polymer exhibits good adhesion properties through the copolymerization reaction of cashew phenol acrylate, double-bonded dopamine and double-bonded rosin acid, and can firmly adhere to the surface of the substrate material, thereby ensuring that the coating tightly covers the substrate material. The mercapto silicone resin is prepared by hydrolytic condensation polymerization of methyltrimethoxysilane, dimethyldimethoxysilane and 3-mercaptopropyltrimethoxysilane. It has a Si-O-Si backbone, which has weather resistance and low friction. The chain segments are flexible and have certain hydrophobic properties due to the low surface energy.
[0016] This invention utilizes the sol-gel method to synthesize titanium-doped hydroxyapatite, and then uses tridecylfluorooctyltriethoxysilane to modify the surface of the titanium-doped hydroxyapatite, preparing hydrophobic-doped co-modified hydroxyapatite. The hydroxyapatite exhibits excellent biocompatibility, and the addition of titanium enhances its light absorption, enabling it to absorb ultraviolet light and generate highly oxidizing reactive oxygen species that disrupt bacterial cell walls and membranes, thus giving the coating antibacterial properties. The grafting of tridecylfluorooctyltriethoxysilane onto the surface of the titanium-doped hydroxyapatite not only imparts hydrophobic properties but also facilitates the uniform distribution of the titanium-doped hydroxyapatite in the matrix material, helping it withstand loads during surface wear and peeling, effectively reducing matrix wear. This invention employs a segmented temperature-controlled heat setting process: first, the proximal end is heated at 350-400℃ and held for 20-25 minutes, then the distal end is heated at 400-500℃ and held for 30 minutes. Simultaneously, the bending curvature is corrected in real time by an elastic pressure head within the mold. After molding, a low-temperature aging treatment (100-150℃, heat preservation for 24 hours) is used to eliminate internal stress, ensuring that the S-bend shape stability reaches over 98%, while maintaining overall straightness. It also provides a superhydrophobic modified coating for morphologically stable S-bend interventional microwires. Based on the excellent properties of polytetrafluoroethylene (PTFE), a mixture of hydrophobic-doped co-modified hydroxyapatite, functionalized polymers, mercaptosilicone resin, and waterborne epoxy resin is used. This coating is firmly bonded to the surface of the interventional microwire through ultraviolet irradiation and thermal curing, exhibiting excellent adhesion and antibacterial properties, while also possessing excellent superhydrophobic properties. Furthermore, it maintains excellent performance even after mechanical wear, enhancing the long-term durability of the material and effectively solving problems such as weak adhesion between the coating and the substrate and easy detachment. Detailed Implementation
[0017] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0018] The present invention provides a stable S-curve interventional microguidewire. The anatomically matched S-curve parameter design is based on the anatomical curvature of blood vessels in different locations (such as cerebral vessels and peripheral vessels). A quantitative adaptation model is established for the S-curve angle, arc length, and two-segment bending radii. A progressive S-curve with a distal end of 30~45° is designed. The length of the bending segment matches 3 times the diameter of the main branch vessel to ensure the natural compliance of the guidewire when entering the branch vessel. The variable stiffness S-curve segment is integrally formed using a gradient stiffness design. The proximal end of the S-curve (closer to the operating end) maintains high stiffness to ensure the transmission of pushing force, while the distal end (head end) uses stainless steel S-curve material. When applied, it can maintain its shape and adapt to the elastic deformation of the vessel wall when passing through the narrow section of the vessel.
[0019] The formed S-bend is reconstructed in three dimensions, and parameters such as bending angle, arc length, and radius are accurately measured with the error controlled within ±0.1mm. Simultaneously, simulated vascular access testing is conducted. 100 passes are performed in a simulated human vascular model, and the S-bend shape retention rate reaches more than 90%. The fatigue life accelerated test is designed to simulate the fatigue test device of repeated bending of blood vessels. The S-bend section of the guidewire is placed in a simulated bending environment with a curvature radius of 5mm and subjected to 10,000 reciprocating bending tests. After the test, the tensile strength of the guidewire decreases by no more than 10%, and the change in S-bend shape does not exceed 5% of the initial value.
[0020] Example 1: A method for preparing a functionalized polymer includes the following steps: (1) Take 32g of cashew phenol glycidyl ether and add it to the reactor, then add 0.08g of hydroquinone and 0.7g of triphenylphosphine. Keep the oil bath temperature at 85°C and slowly add 7.15g of acrylic acid over 4 hours. After the addition is complete, stir the reaction for 6 hours. After the reaction is complete, extract and purify the product with ethyl acetate and saturated sodium bicarbonate solution. Dry the organic phase with anhydrous magnesium sulfate. After the solvent is evaporated under vacuum at 50°C, cashew phenol acrylate is prepared. (2) Dissolve 10g of tetraborate and 4g of sodium bicarbonate in 100mL of deionized water, add 5g of dopamine hydrochloride and stir until well mixed, then slowly add 4.7mL of a mixed solution of methacrylic anhydride and 25mL of tetrahydrofuran. After the reaction is complete, filter the mixed solution, add 50mL of ethyl acetate to the filtrate, adjust the pH to 2 with 6mol / L hydrochloric acid, separate the organic layer, dry with anhydrous magnesium sulfate and rotary evaporate to obtain a concentrated solution, add 300mL of n-hexane to the concentrated solution and mix thoroughly to precipitate a solid precipitate, collect the solid precipitate by centrifugation and dissolve it with ethyl acetate, then wash with n-hexane and vacuum dry to prepare double bond dopamine; (3) Dissolve 6.04 g of rosin acid in 20 mL of ethyl acetate, and then slowly add a mixed solution of 5.08 g of oxaloyl chloride and 5 mL of ethyl acetate under ice bath conditions. Then react at 50°C for 5 h to obtain chlorinated rosin acid. Dissolve 2.79 g of hydroxyethyl acrylate and 4.05 g of triethylamine in 5 mL of ethyl acetate, and then add chlorinated rosin acid. React at 50°C for 4 h. After the reaction is completed, filter to remove the precipitate, collect the solvent layer, wash with saturated brine, and remove the solvent by rotary evaporation to prepare double bond rosin acid. (4) 1.33 mmol cashew phenol acrylate, 1.67 mmol double bond dopamine and 3.88 mmol double bond rosin acid were dissolved in a mixed solution of 20 mL deionized water and 20 mL tetrahydrofuran, and then added to a reactor containing 0.2 mmol 4-cyano-4-(thiobenzoyl)valerate initiator and reacted for 5 h. After the reaction was completed, the mixture was dialyzed for 24 h in a mixed solution of deionized water and anhydrous ethanol with a volume ratio of 1:1 through a 3500 Da dialysis bag, and then dried by rotary evaporation to obtain the functionalized polymer.
[0021] Example 2: A method for preparing a thiol-based organosilicon resin includes the following steps: 4.11 g of methyltrimethoxysilane, 8.04 g of dimethyldimethoxysilane, 9.82 g of 3-mercaptopropyltrimethoxysilane, and 10 g of ethyl acetate were added to a reactor. The temperature was raised to 50°C, and then 0.44 g of hydrochloric acid and 7.5 g of deionized water were slowly added dropwise over 1 hour. The mixture was then maintained at 60°C for 3 hours. After the reaction was completed, the organic phase was washed with deionized water until neutral. The solvent was evaporated under vacuum at 50°C to prepare a mercapto-based organosilicon resin.
[0022] Example 3 A method for preparing hydrophobic-doped co-modified hydroxyapatite includes the following steps: ① Take 2 mL of tetrabutyl titanate and dissolve it in 50 mL of deionized water to fully hydrolyze it to obtain a yellow metatitanic acid precipitate. Then add 10.4 mL of 50% hydrogen peroxide to the metatitanic acid precipitate and sonicate it with an ultrasonic power of 80 W for 10 min to obtain a light yellow sol. At the same time, add 1 mL of acetylacetone and reflux it at 90°C for 20 min to prepare a titanium dioxide hydrosol. ② Take 5g of hydroxyapatite, 22.5mL of deionized water and 2.5mL of titanium dioxide hydrosol and stir to react for 4h. Then filter and dry the product. Add the dried powder to a planetary ball mill for 10min of grinding. After grinding, sieve through 400 mesh. Put the sieved powder into a muffle furnace and calcine at 600°C for 40min to prepare titanium-doped hydroxyapatite. ③ Take 5g of titanium-doped hydroxyapatite and ultrasonically disperse it in 80mL of anhydrous ethanol to obtain a dispersion. Take tridecafluorooctyltriethoxysilane, ethanol and deionized water in a mass ratio of 1:10:1 to prepare a hydrolysate. Adjust the pH of the hydrolysate to 5 using acetic acid, and then slowly add it to the dispersion. Place it at 110°C for 24h. After the reaction is completed, centrifuge, wash and dry to prepare hydrophobic-doped co-modified hydroxyapatite.
[0023] Example 4 A superhydrophobic modified coating comprises the following components in parts by weight: 54 parts of polytetrafluoroethylene, 15.7 parts of hydrophobic-doped co-modified hydroxyapatite prepared in Example 3, 72 parts of waterborne epoxy resin, 21 parts of functionalized polymer prepared in Example 1, 10.8 parts of mercaptosilicone resin prepared in Example 2, 24 parts of curing agent m-phenylenediamine, 2 parts of photoinitiator 2-hydroxy-2-methyl-1-phenyl-1-propanone, and 27 parts of anhydrous ethanol.
[0024] A fabrication process for a morphologically stable interventional microwire with an S-bend includes the following steps: S1. Weigh each component according to the weight parts, and disperse polytetrafluoroethylene and hydrophobic-doped co-modified hydroxyapatite in anhydrous ethanol to form a uniform suspension. S2. Water-based epoxy resin, curing agent, functionalized polymer, mercapto silicone resin and photoinitiator are added to a suspension and stirred evenly to obtain a superhydrophobic modified coating. S3. Cut a 20cm length of stainless steel interventional microwire, and ultrasonically clean it sequentially with acetone, anhydrous ethanol, and deionized water for 15 minutes each. Dry it in an oven and set aside. Transfer the superhydrophobic modified coating to a long test tube (>20cm). Then, pick up the cleaned and dried interventional microwire and immerse it in the superhydrophobic modified coating, slowly pull it up, and then transfer it to 1500mJ / cm. 2 The microwire was photocured under a UV curing machine and then heat-cured in a 60°C oven for 2 hours to prepare a stable S-bend interventional microwire.
[0025] Example 5 A superhydrophobic modified coating comprises the following components in parts by weight: 62 parts of polytetrafluoroethylene, 22.1 parts of hydrophobic-doped co-modified hydroxyapatite prepared in Example 3, 80 parts of waterborne epoxy resin, 29 parts of functionalized polymer prepared in Example 1, 17.7 parts of mercaptosilicone resin prepared in Example 2, 28 parts of curing agent m-phenylenediamine, 2.2 parts of photoinitiator 2-hydroxy-2-methyl-1-phenyl-1-propanone, and 31 parts of anhydrous ethanol.
[0026] The fabrication process of a morphologically stable interventional microwire with an S-bend is the same as in Example 4.
[0027] Example 6 A superhydrophobic modified coating comprises the following components in parts by weight: 72 parts of polytetrafluoroethylene, 28.6 parts of hydrophobic-doped co-modified hydroxyapatite prepared in Example 3, 88 parts of waterborne epoxy resin, 39 parts of functionalized polymer prepared in Example 1, 24.5 parts of mercaptosilicone resin prepared in Example 2, 30 parts of curing agent m-phenylenediamine, 2.4 parts of photoinitiator 2-hydroxy-2-methyl-1-phenyl-1-propanone, and 39 parts of anhydrous ethanol.
[0028] The fabrication process of a morphologically stable interventional microwire with an S-bend is the same as in Example 4.
[0029] Comparative Example 1: A method for preparing a functionalized polymer, which, compared with Example 1, did not add cashew phenol acrylate, and the remaining components and steps were the same as in Example 1.
[0030] Comparative Example 2: A method for preparing a functionalized polymer, which, compared with Example 1, did not add double-bonded dopamine, and the remaining components and steps were the same as in Example 1.
[0031] Comparative Example 3: A method for preparing a functionalized polymer, which, compared with Example 1, did not add double-bonded rosin acid, and the remaining components and steps were the same as in Example 1.
[0032] Comparative Example 4: A superhydrophobic modified coating comprises the following components in parts by weight: 72 parts of polytetrafluoroethylene, 28.6 parts of hydrophobic-doped co-modified hydroxyapatite prepared in Example 3, 88 parts of waterborne epoxy resin, 39 parts of functionalized polymer prepared in Comparative Example 1, 24.5 parts of mercaptosilicone resin prepared in Example 2, 30 parts of m-phenylenediamine curing agent, 2.4 parts of 2-hydroxy-2-methyl-1-phenyl-1-propanone photoinitiator, and 39 parts of anhydrous ethanol.
[0033] The fabrication process of a morphologically stable interventional microwire with an S-bend is the same as in Example 4.
[0034] Comparative Example 5: A superhydrophobic modified coating comprises the following components in parts by weight: 72 parts of polytetrafluoroethylene, 28.6 parts of hydrophobic-doped co-modified hydroxyapatite prepared in Example 3, 88 parts of waterborne epoxy resin, 39 parts of functionalized polymer prepared in Comparative Example 2, 24.5 parts of mercaptosilicone resin prepared in Example 2, 30 parts of m-phenylenediamine curing agent, 2.4 parts of 2-hydroxy-2-methyl-1-phenyl-1-propanone photoinitiator, and 39 parts of anhydrous ethanol.
[0035] The fabrication process of a morphologically stable interventional microwire with an S-bend is the same as in Example 4.
[0036] Comparative Example 6: A superhydrophobic modified coating comprises the following components in parts by weight: 72 parts of polytetrafluoroethylene, 28.6 parts of hydrophobic-doped co-modified hydroxyapatite prepared in Example 3, 88 parts of waterborne epoxy resin, 39 parts of functionalized polymer prepared in Comparative Example 3, 24.5 parts of mercaptosilicone resin prepared in Example 2, 30 parts of m-phenylenediamine curing agent, 2.4 parts of 2-hydroxy-2-methyl-1-phenyl-1-propanone photoinitiator, and 39 parts of anhydrous ethanol.
[0037] The fabrication process of a morphologically stable interventional microwire with an S-bend is the same as in Example 4.
[0038] Comparative Example 7: A superhydrophobic modified coating comprises the following components in parts by weight: 72 parts polytetrafluoroethylene, 28.6 parts hydroxyapatite, 88 parts waterborne epoxy resin, 39 parts functionalized polymer prepared in Example 1, 24.5 parts mercaptosilicone resin prepared in Example 2, 30 parts m-phenylenediamine curing agent, 2.4 parts photoinitiator 2-hydroxy-2-methyl-1-phenyl-1-propanone, and 39 parts anhydrous ethanol.
[0039] The fabrication process of a morphologically stable interventional microwire with an S-bend is the same as in Example 4.
[0040] Performance testing The interventional microwires prepared in Examples 4-6 and Comparative Examples 4-7 were subjected to performance testing: (1) Friction test: The test was conducted using a universal testing machine. The test conditions were: sample length 20cm, sensor 100N, load weight 300g, sample loading speed 50mm / min, loading displacement 150mm. The sample was always in room temperature deionized water throughout the test process. The load changes were recorded throughout the process, and the data results are shown in Table 1.
[0041] (2) Water contact angle test: Fix the sample on the sample platform of the surface contact angle analyzer and test it in the form of a seated drop. The water output should not be too large, set to 1 μL / drop. After the water drop stabilizes, take a picture. Five different positions are selected for each sample and the average value is taken. The data results are shown in Table 1.
[0042] (3) Bonding strength test: The bonding strength of the coating on the sample is characterized by the method of detecting the friction force on the sample surface through multiple frictions. The same sample is tested 40 times at the same location. The average load of each test is recorded using the friction force test method. The data results are shown in Table 1.
[0043] (4) Antibacterial performance test: The antibacterial rate test was carried out in accordance with GB / T 21866-2008. The test species were Escherichia coli and Staphylococcus aureus. The data results are shown in Table 1.
[0044] Table 1 Sample performance test results As can be seen from the data in Table 1, the samples prepared in Examples 4-6 of this invention all have a water contact angle >150°, exhibiting superhydrophobic properties. Simultaneously, they effectively reduce the friction on the sample surface, improve the lubrication performance, thereby reducing friction with patient tissues and thus reducing surgical trauma. Furthermore, the friction force did not change significantly after 40 cycles of friction, demonstrating excellent bonding strength and good antibacterial properties. In Comparative Example 4, the functionalized polymer did not incorporate cashew phenol acrylate, yet its measured friction force was increased compared to Examples 4-6, while its water contact angle was decreased. This is because the unsaturated double bonds on the side chains of cashew phenol acrylate can undergo a mercapto-olefin click reaction with mercapto-silicone resin to construct a polymer main network, thus improving the water contact angle and lubrication performance of the sample. In Comparative Example 5, the functionalized polymer did not incorporate double-bonded dopamine, yet its measured friction force after 40 cycles of friction was significantly increased compared to Examples 4-6, indicating that the introduction of double-bonded dopamine is beneficial for improving the sample's bonding strength. Regarding strength, in Comparative Example 6, the functionalized polymer added did not introduce double-bonded rosin acid, and its measured water contact angle was significantly lower than that of Examples 4-6, indicating that the introduction of double-bonded rosin acid is beneficial to further improve the hydrophobic properties of the sample. In Comparative Example 7, hydrophobic-doped co-modified hydroxyapatite was replaced with an equal amount of hydroxyapatite, and its measured friction force was slightly larger than that of Examples 4-6. The water contact angle, Escherichia coli inhibition rate, and Staphylococcus aureus inhibition rate were lower than those of Examples 4-6, indicating that the introduction of hydrophobic-doped co-modified hydroxyapatite is beneficial to improve the hydrophobic, lubrication, and antibacterial properties of the sample to a certain extent.
[0045] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0046] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the claimed invention.
Claims
1. A fabrication process for a morphologically stable interventional microwire with an S-bend, characterized in that, Includes the following steps: S1. Take 50-75 parts by weight of polytetrafluoroethylene and 15-30 parts by weight of hydrophobic-doped co-modified hydroxyapatite and disperse them in 25-40 parts by weight of anhydrous ethanol to form a uniform suspension. S2. Take 70-90 parts by weight of waterborne epoxy resin, 22-30 parts by weight of curing agent, 20-40 parts by weight of functionalized polymer, 10-25 parts by weight of mercapto silicone resin and 2-2.5 parts by weight of photoinitiator and add them to the suspension. Stir evenly to obtain a superhydrophobic modified coating. S3. The interventional microwire with S-bend is immersed in the superhydrophobic modified coating by dip-coating and pulling method, then transferred to a UV curing machine for photocuring, and then placed in an oven for thermal curing to prepare a morphologically stable interventional microwire with S-bend. The hydrophobic-doped co-modified hydroxyapatite was prepared by synthesizing titanium-doped hydroxyapatite using the sol-gel method, followed by surface modification of the titanium-doped hydroxyapatite using tridecafluorooctyltriethoxysilane; the functionalized polymer was prepared by preparing cashew phenol glycidyl acrylate by ring-opening reaction of cashew phenol glycidyl ether and acrylic acid, followed by polymerization reaction of cashew phenol glycidyl acrylate, dopamine with double bond and rosin acid with double bond; the mercaptosilicone resin was prepared by hydrolytic condensation polymerization of methyltrimethoxysilane, dimethyldimethoxysilane and 3-mercaptopropyltrimethoxysilane.
2. The fabrication process of the morphologically stable S-bend interventional microwire according to claim 1, characterized in that, The interventional microguidewire is made of stainless steel or nickel-titanium alloy.
3. The fabrication process of the morphologically stable S-bend interventional microwire according to claim 1, characterized in that, The distal end of the interventional microguidewire has a progressive S-bend of 30-45°, and the interventional microguidewire undergoes segmented temperature-controlled heat setting treatment. The segmented temperature-controlled heat setting process is as follows: first, the proximal end is heated at 350-400°C and held for 20-25 minutes, then the distal end is heated at 400-500°C and held for 30 minutes. After forming, a low-temperature aging treatment at 100-150°C for 24 hours is used to eliminate internal stress.
4. The fabrication process of the morphologically stable S-bend interventional microwire according to claim 1, characterized in that, The curing agent is an amine curing agent; the photoinitiator is 2-hydroxy-2-methyl-1-phenyl-1-propanone.
5. The fabrication process of the morphologically stable S-bend interventional microwire according to claim 1, characterized in that, The method for preparing the functionalized polymer includes the following steps: (1) Cashew phenol glycidyl ether was added to the reactor, followed by hydroquinone and triphenylphosphine. The oil bath temperature was maintained at 85°C. Acrylic acid was slowly added dropwise over 4 hours. After the addition was completed, the reaction was stirred for 6 hours. After the reaction was completed, the product was purified by extraction with ethyl acetate and saturated sodium bicarbonate solution. The organic phase was dried with anhydrous magnesium sulfate. The solvent was evaporated under vacuum at 50°C to prepare cashew phenol acrylate. (2) Dissolve tetraborate and sodium bicarbonate in deionized water, add dopamine hydrochloride and stir to mix evenly, then slowly add a mixed solution of methacrylic anhydride and tetrahydrofuran. After the reaction is complete, filter the mixed solution, add ethyl acetate to the filtrate, adjust the pH value to 2 with hydrochloric acid, separate the organic layer, dry with anhydrous magnesium sulfate and then rotary evaporate to obtain a concentrated solution, add n-hexane to the concentrated solution and mix thoroughly to precipitate a solid precipitate, centrifuge to collect the solid precipitate and dissolve it with ethyl acetate, then wash with n-hexane and vacuum dry to prepare double bond dopamine; (3) Dissolve rosin acid in ethyl acetate, then slowly add a mixed solution of oxaloyl chloride and ethyl acetate under ice bath conditions, and then react at 50°C for 5 h to obtain chlorinated rosin acid. Dissolve hydroxyethyl acrylate and triethylamine in ethyl acetate, then add chlorinated rosin acid, and react at 50°C for 3-5 h. After the reaction is completed, filter to remove the precipitate, collect the solvent layer, wash with saturated brine, and remove the solvent by rotary evaporation to prepare double bond rosin acid. (4) Dissolve cashew phenol acrylate, double bond dopamine and double bond rosin acid in a mixed solution of deionized water and tetrahydrofuran, and then add it to a reactor containing 4-cyano-4-(thiobenzoyl)valerate initiator and react for 3-5 h. After the reaction is completed, the mixture is dialyzed for 24 h in a mixed solution of deionized water and anhydrous ethanol through a 3500 Da dialysis bag, and then dried by rotary evaporation to obtain the functionalized polymer.
6. The fabrication process of the morphologically stable S-bend interventional microwire according to claim 5, characterized in that, The molar ratio of cashew phenol acrylate, double-bonded dopamine, and double-bonded rosin acid is 1~2:1~2:3~4.
7. The fabrication process of the morphologically stable S-bend interventional microwire according to claim 1, characterized in that, The preparation method of the mercapto-organosilicon resin includes the following steps: Methyltrimethoxysilane, dimethyldimethoxysilane, 3-mercaptopropyltrimethoxysilane and ethyl acetate were added to a reactor, and the temperature was raised to 50°C. Then, hydrochloric acid and deionized water were slowly added dropwise over 1 hour. The mixture was then kept at 60°C for 3 hours. After the reaction was completed, the organic phase was washed with deionized water until neutral. The solvent was evaporated under vacuum at 50°C to prepare a mercapto-based organosilicon resin.
8. The fabrication process of the morphologically stable S-bend interventional microwire according to claim 7, characterized in that, The mass ratio of methyltrimethoxysilane, dimethyldimethoxysilane, 3-mercaptopropyltrimethoxysilane, hydrochloric acid, and deionized water is 1:1.9~2:2.3~2.5:0.1~0.12:1.8~2.
9. The fabrication process of the morphologically stable S-bend interventional microwire according to claim 1, characterized in that, The preparation method of the hydrophobic-doped co-modified hydroxyapatite includes the following steps: ① Dissolve tetrabutyl titanate in deionized water and hydrolyze it to obtain a yellow metatitanic acid precipitate. Then add 50% hydrogen peroxide to the metatitanic acid precipitate and sonicate it with an ultrasonic power of 80W for 10 minutes to obtain a light yellow sol. At the same time, add acetylacetone and reflux at 90°C for 20 minutes to prepare titanium dioxide hydrosol. ② Take hydroxyapatite, deionized water and titanium dioxide hydrosol and stir to react for 4 hours. Then filter and dry the product. Add the dried powder to a planetary ball mill for 10 minutes of grinding. After grinding, sieve through 400 mesh. After sieving, put the powder into a muffle furnace and calcine at 600°C for 40 minutes to prepare titanium-doped hydroxyapatite. ③ Titanium-doped hydroxyapatite was ultrasonically dispersed in anhydrous ethanol to obtain a dispersion. A hydrolysate was prepared by taking tridecafluorooctyltriethoxysilane, ethanol and deionized water. The pH of the hydrolysate was adjusted to 4-6 using acetic acid, and then slowly added to the dispersion. The mixture was placed at 110°C for 24 hours. After the reaction was completed, the mixture was centrifuged, washed and dried to obtain hydrophobic-doped co-modified hydroxyapatite.
10. The fabrication process of the morphologically stable S-bend interventional microwire according to claim 9, characterized in that, The addition ratio of hydroxyapatite, deionized water and titanium dioxide hydrosol is 5g: 17.2~22.5mL: 1.2~3.8mL.